A single-sided polishing and fixing method for large-size lithium tantalate wafers

Through the combination technology of double-sided tape and ceramic disc, combined with the use of press and vacuum pen, the damage and difficulty of removing large-sized lithium tantalate wafers during the polishing process is solved, improving the polishing quality and efficiency, and reducing the cost.

CN118951898BActive Publication Date: 2024-12-13TDG HLDG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411441937.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-13
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the prior art, the single-side polishing and fixing method of large-size lithium tantalate wafers has problems such as easy damage to the wafer and difficulty in taking the wafer after polishing. In addition, traditional wax pasting and vacuum adsorption methods are difficult to ensure the polishing quality and safety during the processing.

Method used

The wafer is fixed with a ceramic disc and a press. The combination of pyrolytic adhesive and pressure sensitive adhesive ensures the uniformity and stability of the wafer and the ceramic disc, and is easily removed at high temperature with a vacuum pen. Wafers to avoid scratches and debris.

Benefits of technology

The yield of single-side polishing processing of large-size lithium tantalate wafers is improved, the processing cost and process is reduced, the flatness of the wafer is ensured, and the residual glue is not required, and the risk of edge collapse and debris is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118951898B_ABST
    Figure CN118951898B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of chip material processing technology, and specifically relates to a single-sided polishing and fixing method for a large-sized lithium tantalate chip, comprising the following steps: washing the chip and the ceramic disk respectively; drying the chip and the ceramic disk, and attaching the pressure-sensitive adhesive on the back of the double-sided tape to the surface of the ceramic disk; attaching the chip to the pyrolytic adhesive on the front of the double-sided tape, and fixing it under pressure; polishing; taking out the chip after heating the ceramic disk, and finally obtaining a large-sized lithium tantalate chip with no damage on the surface. The present invention uses double-sided tape to stick the chip, and cooperates with the design of polishing processing parameters to ensure the bonding strength, stability and polishing quality of the chip, and effectively solves the problem that the chip is easy to be damaged when fixing the large-sized chip in the existing single-sided polishing process, and it is difficult to take the chip after polishing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chip material processing, and in particular relates to a single-side polishing processing and fixing method for a large-size lithium tantalate chip. Background Art

[0002] Lithium tantalate crystals have highly controllable properties and possess excellent piezoelectric effect, photoelectric effect, photorefractive effect and other photoelectric properties. They are very important multifunctional crystal materials. Optoelectronic devices such as surface acoustic wave filters, optical modulators, and Q-switched switches based on lithium tantalate crystals have been widely studied and applied in the fields of communication technology, electronic technology, remote sensing and telemetry.

[0003] The single-sided polishing process is an indispensable processing technology in the preparation of lithium tantalate wafers. The single-sided polishing process can improve the flatness of the wafer and reduce the surface roughness of the wafer. The quality of polishing directly affects the final output quality of the wafer. The existing single-sided polishing process usually uses waxing or vacuum adsorption to fix the wafer during processing. The waxing method generally includes four steps: heating, waxing, pressing, and waxing. The ceramic plate is heated to a certain temperature and waxed to melt. The surface of the waxed wafer is attached to the ceramic plate and a certain pressure is applied. However, it is difficult to ensure the uniformity of the polishing wax when waxing. Bubbles are prone to appear in the wax layer when pressing. The larger the size of the wafer, the larger the bubbles. Continuing to pressurize will cause the wafer to break. After the polishing process is completed, it is necessary to cooperate with a scraper to lift the wafer from the edge of the wafer to remove it. It is very easy to cause missing corners, broken edges, and even fragments during the removal of the wafer. Therefore, the polishing yield of the traditional waxing method is relatively low, which increases the cost of the enterprise. The vacuum adsorption method uses the force formed by the pressure difference between the vacuum system and the atmosphere to fix the wafer, avoiding the tedious waxing and waxing process. It is simple and quick to take and place the wafer, but the Mohs hardness of lithium tantalate is 5.5 and the surface is relatively soft. If there are large particles on the surface of the wafer or the cleanliness of the processing environment is poor during processing, vacuum adsorption will cause pits and scratches on the surface of the wafer, and even produce suction marks at the adsorption groove, reducing the processing yield.

[0004] The invention patent with announcement number CN110400771B designs a method for waxing three-inch wafers. After applying the wax, a dust-free paper ball is used to press the center of the three-inch wafer and circle around the center of the wafer with the center of the wafer as the center point until the bubble diameter is less than 1 mm. This method effectively removes bubbles and controls TTV. At the same time, solid wax is used to control the waxing thickness, but the bubble removal time is long and it is only suitable for three-inch wafers. In addition, the surface thickness uniformity of the solid wax is difficult to ensure after waxing, which affects the processing accuracy. At the same time, this method still cannot avoid the problem of scratches and fragments caused by wafer removal.

[0005] The invention patent with publication number CN115229832A discloses a scratch-proof vacuum adsorption type wafer handling device and a manufacturing method thereof. A buffer gasket is added during the structural design process to prevent scratches on the wafer, but there are problems of residual suction marks and pits after vacuum adsorption.

[0006] The invention patent with publication number US4512113A designs a workpiece fixture for fixing a wafer during polishing, which ensures the flatness of the wafer. However, the fixing material used cannot be reused, and the replacement of the fixing material is complicated, resulting in low processing efficiency and high cost.

[0007] The invention patent with publication number CN106992112A proposes a method for polishing ultra-thin wafers, which increases the thickness of the wafer by coating a colloid on the non-polished surface of the wafer, and controls the exposed thickness of the wafer in conjunction with a template to achieve polishing of the ultra-thin wafer. However, since the wafer is placed inside the groove of the template, the colloid or tape is difficult to arrange and replace, and the edge is easily warped by the erosion of the polishing liquid during the polishing process, and the flatness of the wafer fixation is difficult to ensure.

[0008] Therefore, the existing polishing technology lacks a single-side polishing and fixing method for large-size lithium tantalate wafers that avoids wafer damage and is convenient for wafer removal. Summary of the invention

[0009] The invention provides a single-side polishing processing and fixing method for a large-size lithium tantalate wafer to solve the defects of the prior art. The method has a stable processing process and solves the problems of easy damage to the wafer when the wafer is fixed and difficulty in taking out the wafer after polishing in the prior polishing process.

[0010] A single-side polishing and fixing method for a large-size lithium tantalate wafer comprises the following steps:

[0011] Step a): cleaning the wafer and the ceramic disk separately, wherein the diameter of the wafer is greater than 100 mm;

[0012] Step b): drying the wafer and ceramic disk processed in step a), tearing off the release film on the back of the double-sided tape, the back of the double-sided tape being a pressure-sensitive adhesive, applying the pressure-sensitive adhesive to the surface of the ceramic disk, and compacting the applied surface;

[0013] Step c): tear off the release film on the front side of the double-sided tape, the front side of the double-sided tape is a pyrolytic adhesive, heat the ceramic plate to 58-62°C, attach the back side of the wafer to the front side of the double-sided tape, pressurize the attached surface, and stop pressurizing after the temperature of the ceramic plate drops below 40°C;

[0014] Step d): After checking that there are no bubbles or wrinkles on the contact surfaces of the ceramic disc, double-sided tape, and wafer, the ceramic disc of step c) is placed on a polishing table for polishing at a polishing pressure of 100 g / cm 2 ~500g / cm2 , polishing liquid flow rate 5 ~ 10L / min, the chip temperature is maintained at 25 ~ 30 ℃;

[0015] Step e): After polishing is completed, the ceramic disk is taken out and heated to 63-65° C., and the wafer is removed using a vacuum pen.

[0016] In the above step a), the wafer and the ceramic disk are respectively placed in a cleaning solution for ultrasonic cleaning for 5 to 15 minutes at an ultrasonic frequency of 30 to 50 kHz to clean the surface particles of the wafer and the ceramic disk. Then the wafer and the ceramic disk are respectively placed in a pure water tank for rinsing for 2 to 5 minutes to remove the residual cleaning solution.

[0017] In the above step a), the wafer and the ceramic disk are cleaned respectively to ensure the surface cleanliness of the wafer and the ceramic disk to avoid contamination on the surface of the wafer or the ceramic disk, which may cause pits or scratches on the wafer during polishing. The diameter of the ceramic disk is larger than the diameter of the wafer, and a single ceramic disk can evenly place 3 to 30 wafers.

[0018] Among them, in step a), the cleaning solution is mixed by pure water and alkaline cleaning agent in a volume ratio of 5 to 20:1, and the mass fractions of the components constituting the alkaline cleaning agent are 55 to 70% pure water, 15 to 35% potassium hydroxide, 5 to 15% chelating agent, 3 to 12% surfactant, and 1 to 5% buffer.

[0019] In the above step b), the chip and the ceramic disk are dried to prevent residual water stains from affecting the stickiness of the double-sided tape. The back of the double-sided tape is a pressure-sensitive adhesive that is resistant to high temperature and corrosion and is not prone to residual adhesive. After it is attached to the surface of the ceramic disk, a rubber roller is used to slowly apply pressure from one edge of the chip to the other side with a uniform force, and then it is compacted with a press to increase the bonding strength and ensure that the film can be completely attached to the surface of the ceramic disk, and there are no bubbles or wrinkles on the surface. When attaching the tape, ensure that the tape area is larger than the ceramic disk area, and fix the excess tape to the outer edge or back of the ceramic disk to prevent the polishing liquid from entering the edge of the tape or generating bubbles during polishing, which affects the bonding strength and polishing effect.

[0020] In the above step b), the front side of the double-sided tape is a pyrolytic adhesive, the middle of the pressure-sensitive adhesive and the pyrolytic adhesive is a PET film, the surfaces of the pressure-sensitive adhesive and the pyrolytic adhesive are provided with release films, the pressure-sensitive adhesive components include epoxy resin, rosin ester, filler, phenyl benzoate, antioxidant, polythiol, additives, nanoparticles, and the adhesion is 9.5-10.5N / 25mm; the pyrolytic adhesive components include polyvinyl alcohol, toughening plasticizer, acrylate, modified ammonia, additives, preservatives, fillers, nanoparticles, the adhesion of the tape is 8.5-10N / 25mm when the temperature is below 40°C, and the adhesion becomes 0.05-0.2N / 25mm when heated to 58-62°C, and the nanoparticles are one or both of nano-silicon dioxide and nano-alumina, which are used to improve the stability and conductivity of the tape.

[0021] Wherein, in step b), the mass fractions of the components of the pressure-sensitive adhesive are 30-45% of epoxy resin, 2-8% of rosin ester, 10-15% of filler, 5-15% of phenyl benzoate, 3-10% of antioxidant, 3-10% of polythiol, 5-15% of auxiliary agent, and 5-10% of nanoparticles; the mass fractions of the components of the pyrolytic adhesive are 35-45% of polyvinyl alcohol, 3-10% of toughening plasticizer, 5-15% of acrylate, 5-10% of modified ammonia, 3-10% of auxiliary agent, 3-10% of preservative, 10-15% of filler, and 5-10% of nanoparticles.

[0022] In the above step c), the ceramic plate is heated to 58-62°C, and the coated surface is pressurized at a pressure of 100-5000N. After maintaining the temperature for 3-5 minutes, the heating of the ceramic plate is stopped, and the pressurization is stopped when the temperature of the ceramic plate drops below 40°C;

[0023] In the above step c), the temperature is raised to 58-62°C to soften the glue, and the tape becomes softer and easier to contact with the chip surface and adapt to its shape. At this time, the contact effect between the chip and the tape is better. At the same time, a press is used to pressurize the pasted surface to ensure the uniformity of the chip and the ceramic disk and avoid bubbles in the contact interface. After the temperature drops below 40°C, the glue crystallizes and is fixed with a press to ensure that the chip is in full contact with the tape. At the same time, the film is flat, free of bubbles and wrinkles, and the surface deviation of the chip after pasting is less than 1μm.

[0024] In the above step d), during the polishing process, the characteristics of the wafer and the tape itself are combined to ensure the strength and stability of the tape adhesion while ensuring the polishing quality. The function of the pressure-sensitive adhesive on the back of the double-sided tape is to firmly fix the back of the tape on the ceramic disk. Under normal circumstances, the adhesion of the pressure-sensitive tape is positively correlated with the applied pressure. The greater the polishing pressure during polishing, the stronger the adhesion of the pressure-sensitive adhesive, the closer the contact between the polishing pad and the wafer, and the higher the wafer removal rate. However, due to the low hardness and high brittleness of large-inch lithium tantalate wafers, excessive processing pressure can easily cause scratches, damage, and even fragments on the wafer surface. In order to ensure adhesion strength and stability and improve the surface quality of the wafer, preferably, the polishing pressure is 200g / cm 2 ~400g / cm 2 More preferably, the polishing pressure is 250 g / cm 2 ~350g / cm 2 .

[0025] In the above step d), since the front side of the double-sided tape is a thermally debonding tape, in order to avoid the local temperature of the chip being too high during the polishing process, causing the tape to lose its viscosity or reduce its viscosity, the chip temperature during polishing is controlled at 25-30°C; preferably, the polishing liquid is one or more of SiO2, Al2O3, CeO2, and the polishing liquid flow rate is 6.5-8.5L / min, preferably, the polishing liquid flow rate is 7-8L / min, and the flow rate is controlled so that the polishing liquid can promptly take away the heat generated by polishing. The pH value of the polishing liquid is 8.5-11.5 to avoid excessive pH affecting the viscosity of the tape.

[0026] In the above step e), the ceramic disk is heated to 63-65°C. Since the lithium tantalate wafer has pyroelectric properties and low hardness, high temperature or too fast heating can easily cause fragments or generate stress inside the wafer. The wafer is large in size and is easily affected by thermal stress during the heating process. The temperature uniformity of the wafer is difficult to ensure. A temperature gradient is likely to occur inside the wafer. The expansion coefficients of different regions may also differ, which will cause thermal stress inside the wafer. It is very easy to break during subsequent polishing. Therefore, the temperature is slowly increased step by step during heating, first increasing to 38-40°C at 1.5-2°C / min, then increasing to 50-52°C at 1-1.3°C / min, and finally increasing to 63-65°C at 0.5-0.8°C / min to ensure that the tape completely loses its stickiness. At this time, the adhesive force of the tape is less than 0.2N / 25mm. The wafer can be easily removed using a vacuum suction pen without using tools such as a spatula, thereby avoiding defects such as scratches and edge collapse of the wafer when taking the wafer. There is no residual glue on the surface of the wafer, and no cleaning and degumming processes are required, thereby improving processing efficiency and ensuring wafer quality.

[0027] Among them, the pyrolytic adhesive can be reused. When the temperature of the ceramic disc drops below 40°C, the pyrolytic adhesive regains its viscosity. If processing is required, continue to paste the patch at a ceramic disc temperature of 58-62°C, use a rubber roller and a press to pressurize the pasted surface, maintain the temperature of the ceramic disc for 3-5 minutes and then stop heating. Stop pressurizing when the temperature of the ceramic disc drops to 40°C, and then place the ceramic disc on the polishing table to continue processing. There is no need to replace the tape. The double-sided tape can be reused 5-8 times. After 8 uses, the adhesion on the front of the tape is tested to be greater than 6N / 25mm, and it can continue to be used, which improves processing efficiency and reduces processing costs.

[0028] A single-side polishing processing and fixing method for a large-size lithium tantalate wafer can also be used for rework polishing of a double-sided polished wafer with unqualified single-side quality, thereby reducing polishing costs and improving processing efficiency.

[0029] Compared with the prior art, the present invention has the following beneficial technical effects:

[0030] In the first aspect, the present invention provides a single-sided polishing and fixing method for a large-sized lithium tantalate wafer, which uses a double-sided tape in conjunction with a press to fix the tape and the wafer, and there are no bubbles at the contact interface of the ceramic disk, the tape, and the wafer, and there are no defects such as edge collapse, scratches, and suction marks during the processing. The processing yield is high and the method is suitable for single-sided polishing of lithium tantalate wafers with a diameter greater than 100 mm;

[0031] In the second aspect, the present invention proposes a single-sided polishing and fixing method for a large-sized lithium tantalate wafer. After polishing, no tools such as a scraper are needed to remove the wafer. The ceramic plate is heated to 63-65°C, and the front side of the double-sided tape loses its stickiness. The wafer can be easily removed using a vacuum suction pen without the risk of edge collapse.

[0032] In the third aspect, the present invention proposes a single-sided polishing and fixing method for a large-sized lithium tantalate wafer, which uses double-sided tape to replace traditional polishing wax, thereby avoiding the problem of uneven wax application. The surface deviation after film application is less than 1 μm, and there is no residual glue on the surface of the wafer after polishing, and no degumming cleaning, drying and other processes are required, which greatly reduces the processing steps and improves the processing efficiency.

[0033] Fourthly, after the wafer is polished, the ceramic disk does not need to be cleaned, and the double-sided tape can be reused multiple times, thus avoiding the cumbersome steps of traditional repeated waxing and cleaning, improving processing efficiency and reducing processing costs;

[0034] In the fifth aspect, the double-sided tape used in the present invention has a pressure-sensitive adhesive on the back and a pyrolytic adhesive on the front. By combining the characteristics of the tape and the large-size lithium tantalate wafer, unique polishing processing parameters are set to ensure the bonding strength, stability and polishing quality of the wafer;

[0035] In a sixth aspect, the single-sided polishing processing and fixing method for large-size lithium tantalate wafers proposed in the present invention can also be applied to rework polishing of double-sided polished wafers with unqualified single-sided quality, thereby reducing polishing costs and improving processing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the processing flow of the present invention;

[0037] Figure 2 It is a schematic diagram of the structure of the double-sided tape of the present invention;

[0038] Figure 3 It is a schematic diagram of pressurization of the press machine of the present invention;

[0039] In the figure: 1-front release film of double-sided tape; 2-pyrolytic adhesive; 3-PET film; 4-pressure-sensitive adhesive; 5-release film on the back of double-sided tape; 6-upper pressure cover plate; 7-rubber gasket; 8-wafer; 9-double-sided tape; 10-ceramic disk; 11-rubber gasket; 12-lower pressure cover plate. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with the embodiments, but the protection scope of the present invention shall not be limited thereto.

[0041] Example 1 is as follows:

[0042] Figure 1 It is a schematic diagram of the processing flow of the present invention, according to Figure 1 The process is used to fix and polish the wafer.

[0043] Step a): prepare an alkaline cleaning agent according to the mass fraction of 55% pure water, 25% sodium hydroxide, 10% chelating agent, 7% surfactant and 3% buffer, prepare a cleaning solution according to the volume ratio of pure water to alkaline cleaning agent of 10:1, put the 8-inch wafer 8 and the ceramic disk 10 into the cleaning solution for 40 kHz ultrasonic cleaning for 10 minutes, clean the surface particles of the wafer 8 and the ceramic disk 10, and then put the wafer 8 and the ceramic disk 10 into a pure water tank for rinsing for 3 minutes to remove the residual cleaning solution on the surface;

[0044] Step b): Figure 2 Schematic diagram of the structure of the double-sided tape of the present invention, wherein a PET film 3 is provided between the pyrolytic adhesive 2 and the pressure-sensitive adhesive 4; the wafer 8 and the ceramic disk 10 are dried, the release film 5 on the back of the double-sided tape is torn off, and the pressure-sensitive adhesive 4 containing 40% epoxy resin, 7% rosin ester, 13% filler, 10% phenyl benzoate, 7% antioxidant, 8% polythiol, 10% additive, and 5% nanoparticles by mass is applied to the surface of the ceramic disk 10, and a roller is used to slowly apply pressure from one side of the reference edge of the wafer 8 to the other side with uniform force, and then a press is used to compact the applied surface to ensure that there are no bubbles or wrinkles at the applied interface;

[0045] Step c): tear off the release film 1 on the front side of the double-sided tape, the mass fractions of the components of the pyrolytic adhesive 2 are 45% polyvinyl alcohol, 5% toughening plasticizer, 10% acrylate, 5% modified ammonia, 5% additive, 5% preservative, 15% filler, and 10% nanoparticles, heat the ceramic plate 10 to 60°C, use a chip mounter to attach the back side of the chip 8 to the front side of the double-sided tape 9, use a rubber roller to slowly apply pressure from one edge of the chip 8 to the other side with uniform force, and then press Figure 3 The laminating surface is pressurized with 1000N by a press machine, the press machine has an upper pressure cover plate 6 and a lower pressure cover plate 12, and is provided with rubber gaskets 7 and rubber gaskets 11 to prevent the pressure cover plate from damaging the wafer 8 and the ceramic plate 10. After maintaining the temperature at 60°C for 5 minutes, the ceramic plate 10 is stopped from being heated, and the pressurization is stopped when the temperature of the ceramic plate 10 drops to 30°C;

[0046] Step d): After checking that there are no bubbles or wrinkles on the contact surface of the ceramic disk 10, the double-sided tape 9 and the wafer 8, the ceramic disk 10 after the bonding in step c) is placed on the polishing table for polishing at a polishing pressure of 300 g / cm 2 , polishing liquid flow rate 8L / min, polishing liquid pH value 9, wafer 8 temperature maintained at 30°C;

[0047] Step e): After polishing is completed, the ceramic disk 10 is taken out, heated to 40° C. at 2° C. / min, then heated to 50° C. at 1° C. / min, and finally heated to 65° C. at 0.5° C. / min, and the wafer 8 is removed using a vacuum pen.

[0048] After the polishing process in this embodiment, the wafer was inspected to have no edge collapse and fragmentation, and the surface quality was good, with a scratch rate of 0.9%, a pit rate of 0.3%, and an overall qualified rate of 98.8%.

[0049] Example 2 is as follows:

[0050] Step a): prepare an alkaline cleaning agent according to the mass fraction of 55% pure water, 25% sodium hydroxide, 10% chelating agent, 7% surfactant, and 3% buffer, prepare a cleaning solution according to the volume ratio of pure water to alkaline cleaning agent of 10:1, put the 6-inch wafer 8 and the ceramic disk 10 into the cleaning solution respectively and perform 40 kHz ultrasonic cleaning for 10 minutes to clean the particle contamination on the surface of the wafer 8 and the ceramic disk 10, and then put the wafer 8 and the ceramic disk 10 into a pure water tank respectively and rinse for 3 minutes to remove the residual cleaning solution on the surface;

[0051] Step b): same as in Example 1;

[0052] Step c): tear off the release film 1 on the front side of the double-sided tape, the mass fractions of the components of the pyrolytic adhesive 2 are 45% polyvinyl alcohol, 5% toughening plasticizer, 10% acrylate, 5% modified ammonia, 5% additive, 5% preservative, 15% filler, and 10% nanoparticles, heat the ceramic disk 10 to 60°C, use a placement machine to stick the non-reworked surface of the double-polished wafer 8 on the front side of the double-sided tape 9, use a rubber roller to slowly apply pressure from one edge of the wafer 8 to the other side with uniform force, and then use a press to pressurize the attached surface with 1000N, keep the temperature at 60°C for 5 minutes, then stop heating the ceramic disk 10, and stop pressing when the temperature of the ceramic disk 10 drops to 30°C;

[0053] Step d): same as in Example 1;

[0054] Step e): Same as Example 1.

[0055] In this embodiment, the non-rework surface of the double-sided polished wafer is attached to the front side of the double-sided tape to complete the single-sided re-polishing of the unqualified double-sided polished wafer. Compared with the re-polishing process using a double-sided polishing machine, the processing efficiency is improved and the problem of chip edge fragmentation caused by using a planetary wheel to fix the wafer during double-sided polishing (the edge of the wafer is prone to collide with the planetary wheel during double-sided polishing) is avoided.

[0056] In order to highlight the beneficial effects of the present invention, the following comparative example experiments were also carried out.

[0057] Comparative Example 1:

[0058] Step a): same as in Example 1;

[0059] Step b): same as in Example 1;

[0060] Step c): Same as Example 1, except that the heating temperature of the ceramic plate is 40° C.;

[0061] Step d): same as in Example 1;

[0062] Step e): Same as Example 1.

[0063] After inspection, the scratch rate of the chip after polishing in this comparative example was 2.5%, the edge chipping rate was 1.1%, and the fragmentation rate was 2.9%. The scratch rate, edge chipping rate, and fragmentation rate all increased. The reason was analyzed as follows: when the heating temperature of the ceramic disk was low, the tape did not soften, and the adhesion effect between the chip and the tape was poor. There may be problems with uneven patch or bubbles on the contact surface, which led to a slight increase in the scratch rate, edge chipping rate, and fragmentation rate during the polishing process.

[0064] Comparative Example 2:

[0065] Step a): same as in Example 1;

[0066] Step b): same as in Example 1;

[0067] Step c): Same as Example 1, except that the heating temperature of the ceramic plate is 85° C.;

[0068] Step d): same as in Example 1;

[0069] Step e): Same as Example 1.

[0070] After inspection, the scratch rate of the chips after polishing in this comparative example was 3.4%, the edge chipping rate was 2.8%, and the fragmentation rate was 6.7%. The scratch rate, edge chipping rate, and fragmentation rate increased significantly. The reason for this was analyzed to be that the lithium tantalate chip had a low Mohs hardness and also had pyroelectricity. When the heating temperature of the ceramic disk was too high, stress concentration was caused due to the temperature difference, and fragmentation, scratches, and edge chipping were more likely to occur during subsequent processing.

[0071] Comparative Example 3:

[0072] Step a): same as in Example 1;

[0073] Step b): same as in Example 1;

[0074] Step c): same as in Example 1;

[0075] Step d): Same as Example 1, except that the polishing pressure is 800 g / cm 2 ;

[0076] Step e): Same as Example 1.

[0077] After inspection, the scratch rate of the chips after polishing in this comparative example was 5.6%, the edge collapse rate was 1.6%, the fragmentation rate was 11.3%, and the pit rate was 3.9%. The scratch rate, fragmentation rate, and pit rate increased significantly. The reason was analyzed as the polishing pressure of this comparative example was too high, the stress distribution inside the 8-inch lithium tantalate chip was more complicated, and the excessive polishing pressure caused the scratch rate, fragmentation rate, and pit rate to increase significantly.

[0078] Comparative Example 4:

[0079] Step a): same as in Example 1;

[0080] Step b): same as in Example 1;

[0081] Step c): same as in Example 1;

[0082] Step d): Same as Example 1, except that the polishing pressure is 50 g / cm 2 ;

[0083] Step e): Same as Example 1.

[0084] After inspection, the chips in this comparative example had a scratch rate of 2.5%, a chipping rate of 0.4%, a fragmentation rate of 1.9%, and a pit rate of 4.6%. The pit rate increased relatively. The reason for this was analyzed to be that the polishing pressure in this comparative example was relatively small, the back side of the double-sided tape had less stickiness, and tiny bubbles were generated during the polishing process, causing pits on the chip surface.

[0085] Comparative Example 5:

[0086] Step a): same as in Example 1;

[0087] Step b): same as in Example 1;

[0088] Step c): same as in Example 1;

[0089] Step d): Same as Example 1, except that the polishing liquid flow rate is 3 L / min;

[0090] Step e): Same as Example 1.

[0091] After inspection, the scratch rate of the chip after polishing in this comparative example was 1.6%, the edge collapse rate was 0.5%, the fragmentation rate was 1.2%, and the pit rate was 4.5%. The pit rate increased relatively. The reason was analyzed as the flow rate of the polishing liquid in this comparative example was too low, which could not take away the heat generated by the polishing process in time. The local temperature of the chip was too high, which caused the viscosity of the tape to decrease or bubbles to form, resulting in an increase in the pit rate.

[0092] Comparative Example 6:

[0093] Step a): same as in Example 1;

[0094] Step b): heating the ceramic plate to 80° C., applying a wax layer on the surface of the ceramic plate, and attaching the wafer to the ceramic plate using a chip mounter;

[0095] Step c): using a press machine to press the wafer, and after the pressing is completed, using a single-side polishing machine to polish it;

[0096] Step d): After polishing, the ceramic disk is placed in a cleaning solution for 40 kHz ultrasonic cleaning for 10 minutes. After the cleaning is completed, the wafer is removed from the ceramic disk using a scraper;

[0097] Step e): prepare an alkaline cleaning agent according to the mass fraction of 10% inorganic base, 15% chelating agent, 8% inorganic auxiliary agent, 7% organic base and 60% pure water, mix the alkaline cleaning solution according to the volume ratio of pure water and alkaline cleaning agent of 10:1, put the lithium tantalate wafer into the alkaline cleaning solution at 50°C and perform 40kHz ultrasonic cleaning for 20 minutes to remove the residual wax on the surface.

[0098] This comparative example uses the traditional waxing method to fix the chip. After inspection, the scratch rate is 3.6%, the edge collapse rate is 5.1%, the fragmentation rate is 2.8%, the pit rate is 1.5%, and the polishing quality is poor. This is mainly because the surface uniformity is difficult to ensure and there are bubbles when waxing, resulting in a high scratch rate and fragmentation rate. After polishing, a scraper is used to lift the chip from the edge of the chip and then remove it. Since lithium tantalate is brittle, using a scraper to remove the chip causes an increase in the edge collapse rate.

[0099] Comparative Example 7:

[0100] Step a): prepare an alkaline cleaning agent according to the mass fraction of 55% pure water, 15% inorganic base, 10% chelating agent, 10% inorganic auxiliary agent, and 10% organic base, prepare a cleaning solution according to the volume ratio of pure water to alkaline cleaning agent of 3:1, put the wafer into the cleaning solution for 40 kHz ultrasonic cleaning for 10 minutes to clean the particle contamination on the surface of the wafer, and then put the wafer into a pure water tank for rinsing to remove the residual cleaning solution on the surface;

[0101] Step b): The polishing machine robot places the cleaned lithium tantalate wafer on the vacuum chuck for polishing;

[0102] Step c): After polishing is completed, the robot takes out the wafer and puts it into the flower basket.

[0103] This comparative example uses a vacuum adsorption method to fix the wafer. After inspection, the scratch rate is 1.6%, the edge collapse rate is 0%, the fragmentation rate is 0%, the pit rate is 1%, the suction mark rate is 2.1%, and the overall qualified rate is 95.7%. No edge collapse or fragments are generated, but vacuum adsorption causes suction marks and pits on the surface of some wafers.

[0104] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A single-sided polishing and fixing method for a large-size lithium tantalate wafer, characterized in that: The following steps are involved: Step a): cleaning the wafer and the ceramic disk separately, wherein the diameter of the wafer is greater than 100 mm; Step b): drying the wafer and ceramic disk processed in step a), tearing off the release film on the back of the double-sided tape, and applying the pressure-sensitive adhesive on the back of the double-sided tape to the surface of the ceramic disk, and compacting the applied surface, wherein the pressure-sensitive adhesive has an adhesion of 9.5-10.5 N / 25 mm, and the mass fractions of the components constituting the pressure-sensitive adhesive are 30-45% of epoxy resin, 2-8% of rosin ester, 10-15% of filler, 5-15% of phenyl benzoate, 3-10% of antioxidant, 3-10% of polythiol, 5-15% of additive, and 5-10% of nanoparticles; Step c): tear off the release film on the front side of the double-sided tape, the front side of the double-sided tape is a pyrolytic adhesive, heat the ceramic disk to 58-62°C, attach the back side of the wafer to the front side of the double-sided tape, pressurize the attached surface, the pressure is 100-5000N, keep it at this temperature for 3-5min, stop heating the ceramic disk, and stop pressurizing when the temperature of the ceramic disk drops below 40°C, wherein the pressure-sensitive adhesive and the pyrolytic adhesive are in the middle of a PET film, with a release film on the surface, and the adhesion of the pyrolytic adhesive at a temperature below 40°C is 8.5-10N / 25mm, The adhesive force when heated to 58-62°C becomes 0.05-0.2N / 25mm. The components of the pyrolytic adhesive include polyvinyl alcohol, toughening plasticizer, acrylate, modified ammonia, additives, preservatives, fillers, and nanoparticles. The nanoparticles are one or two of nano-silicon dioxide and nano-alumina. The mass fraction of each component is 35-45% of polyvinyl alcohol, 3-10% of toughening plasticizer, 5-15% of acrylate, 5-10% of modified ammonia, 3-10% of additives, 3-10% of preservatives, 10-15% of fillers, and 5-10% of nanoparticles. Step d): After checking that there are no bubbles or wrinkles on the contact surfaces of the ceramic disc, double-sided tape, and wafer, the ceramic disc of step c) is placed on a polishing table for polishing at a polishing pressure of 100 g / cm 2 ~500g / cm 2 , the polishing liquid flow rate is 5-10L / min, and the chip temperature is maintained at 25-30℃; Step e): After polishing is completed, the ceramic disc is taken out and heated to 63-65°C, wherein the temperature is first increased to 38-40°C at 1.5-2°C / min, then increased to 50-52°C at 1-1.3°C / min, and finally increased to 63-65°C at 0.5-0.8°C / min to ensure that the tape loses its stickiness. At this time, the adhesion on the front side of the tape is less than 0.2N / 25mm, and then a vacuum suction pen is used to remove the chip.

2. A method for single-sided polishing and fixing of a large-size lithium tantalate wafer as claimed in claim 1, characterized in that: In the step a), the wafer and the ceramic disk are respectively placed in a cleaning solution for ultrasonic cleaning for 5 to 15 minutes, with an ultrasonic frequency of 30 to 50 kHz, and then the wafer and the ceramic disk are respectively placed in a pure water tank for rinsing for 2 to 5 minutes to remove residual cleaning solution.

3. A single-side polishing and fixing method for a large-size lithium tantalate wafer as claimed in claim 2, characterized in that: In the step a), the cleaning solution is prepared by mixing pure water and an alkaline cleaning agent in a volume ratio of 5 to 20:1, and the mass fractions of the components constituting the alkaline cleaning agent are 55 to 70% pure water, 15 to 35% potassium hydroxide, 5 to 15% chelating agent, 3 to 12% surfactant, and 1 to 5% buffer.

4. A method for single-side polishing and fixing of a large-size lithium tantalate wafer as claimed in claim 1, characterized in that: In the step d), the polishing pressure is 200 g / cm 2 ~400g / cm 2 , polishing liquid flow rate is 6.5~8.5L / min.

5. A method for single-side polishing and fixing of a large-size lithium tantalate wafer as claimed in claim 1, characterized in that: In the step d), the polishing liquid is one or more of SiO, Al2O3, and CeO2, and the pH value of the polishing liquid is 8.5-11.5.